Impact of information display on worker performance for wood frame wall assembly using AR HMD under different task conditions. (October 2021) - Qin, Y.; Bloomquist, E.; Bulbul, T.; Gabbard, J.; Tanous, K.
Abstract: Augmented Reality (AR) head-mounted displays (HMDs) provide users with an immersive virtual experience in the real world. The portability of this technology affords various information display options for construction workers that are not possible otherwise. However, the impact of these different information presentation options on human performance should be carefully evaluated before such technology is deployed in the jobsite. In this paper, we describe a research effort examining how different information displays presented via AR HMD influence task performance when assembling three sized wooden wall frame assembly tasks. We asked 18 construction engineering students with framing experience to finish three wood frame assembly tasks ( large, medium, and small ) using one of the three information displays ( AR 3D conformal, AR 2D tag-along, and paper blueprints ). The task performance was measured by time of completion and framing errors, which were analyzed and compared among each factor.